The Minimum Boundary Dominating Energy of a Graph - Mohammed Alatif; Puttaswamy (International Journal of Mathematics And its Applications, 2016)
For a graph G, a subset B of V(G) is called a boundary dominating set if every vertex of V(G)- S is vertex boundary dominated by some vertex of S . The boundary domination number γ_b(G) of G is the minimum cardinality of minimum boundary dominating set in G. In this paper we introduce the minimum boundary dominating energy E_B(G) of a graph G and computed minimum boundary dominating energies of some standard graphs. Upper and lower bounds for E_B(G) are established.